Neuroprotective Effect of Danhong Injection on Cerebral Ischemia-Reperfusion Injury in Rats by Activation of the PI3K-Akt Pathway - Feng, Chen; Wan, Haofang; Zhang, Yangyang; Yu, Li; Shao, Chongyu; He, Yu; Wan, Haitong; Jin, Weifeng (Frontiers in Pharmacology, 2020)
Many traditional Chinese medicines, including Danhong injection (DHI), can be used to treat cerebral ischemia-reperfusion injury and have neuroprotective effects on the brain; however, few studies have explored the mechanism by which this effect is generated. In this study, we investigated the neuroprotective effect of DHI against cerebral ischemia-reperfusion injury mediated via the PI3K-Akt signaling pathway. reduced in the DHI group, and the brain function score was significantly improved. In addition, the expression of pro-apoptotic factors (Bad, Bax and Bim) was significantly downregulated in the DHI group, while expression of the anti-apoptotic factor Bcl-2 was significantly upregulated, and expression of the apoptotic gene p53 was also significantly attenuated. Moreover, this neuroprotective effect was attenuated by the PI3K-Akt signaling pathway inhibitor (LY294002). Thus, our results confirmed the neuroprotective effects of DHI in rats with ischemia-reperfusion injury and indicate that these effects on the brain are partly generated by activation of the PI3K-Akt signaling pathway.